Оптический аттенюатор - Doctorovych, I. V.; Fodchuk, I. M.; Butenko, V. K.; Hodovaniouk, V. M.; Yuryev, V. H. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
A precision optical attenuator is described, designed for use in installations measuring the parameters of transmitting and receiving modules of fiber-optic communication lines.